KETIDAKADILAN JENDER YANG DIALAMI PEKERJA PEREMPUAN DI DAERAH PARIWISATA - I MADE WIRARTHA (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2000)
Gender isn’t a difference of sex or god’s will, but is something that is oriented himand her by means of social and culture process in long term. The power of woman in tourismsector is very interesting to be solved. According to conventional, tourism sector is publicsector, that is a man area, but a woman area is domestic sector. Based on tourismdevelopment in Bali, there are many jobs opportunity that can be entered by womancommunity. In fact it will be affected by gender problem.Gender problem in this paper is studied based on research in two villages whichdifferent development tourism at Ubud, Gianyar, Bali. The result of the research shows thatthe woman worker in tourism sector are discriminated which is reflected by lower level wagethan man worker although they have same education and or same job position.